(untitled) (Journal of the College of Basic Education, 2022)
Access to information is subject to ebbs and flows in any country; Is thatThe process of transformation has begun and it is no longer possible to tell citizens that knowledge is not worth itfor them. A new era of government transparency has begun. It became widely knownToday, the culture of secrecy that used to shape the way governments operate is at a stretchYears are no longer applicable in the global age of information and therefore ofIt is necessary for governments in the information age to provide information in order toSuccess.